Improved Isolation Optimizes Downstream Application of Extracellular Vesicles Derived from Mycobacterium tuberculosis - Wenjing Wang; Yue Hou; Jingfang Zhang; Zhaogang Sun; Hong Sun (Microorganisms)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis, secretes extracellular vesicles (EVs), which may play an important role in mediating interactions between bacteria and host cells. Mtb EVs can be isolated by means of various techniques, which differ in terms of their effectiveness. In the present study, we found that an exosome isolation kit (EI) yielded higher numbers of EVs than either differential centrifugation (DC) or exosome detection via an ultrafast-isolation system (EXODUS). We also found that the EXODUS method revealed a greater abundance of H37Rv components within EVs, compared with the DC and EI methods. Analysis of the downstream application of H37Rv EVs revealed their internalization by RAW264.7 macrophages, peaking at 6 h, with subsequent activation of the TLR2 signaling pathway leading to the expression of inflammatory cytokines including IL-6 and TNF-α. It was also found that H37Rv EVs could cross the blood–brain barrier (BBB) and enter the brain, peaking at 12 h post-injection, eliciting an inflammatory response in the cerebral parenchyma, cerebellum, and hippocampus that persisted for up to 6 days. These findings offer novel insights into the pathogenesis of Mtb-induced diseases and may guide the development of therapeutic strategies.